Payload charging events in the mesosphere and their impact on Langmuir type electric probes - Bekkeng, T. A.; Barjatya, A.; Hoppe, U.-P.; Pedersen, A.; Moen, J. I.; Friedrich, M.; Rapp, M. (Annales Geophysicae, 2013)
Three sounding rockets were launched from Andøya Rocket Range in the ECOMA campaign in December 2010. The aim was to study the evolution of meteoric smoke particles during a major meteor shower. Of the various instruments onboard the rocket payload, this paper presents the data from a multi-Needle Langmuir Probe (m-NLP) and a charged dust detector. The payload floating potential, as observed using the m-NLP instrument, shows charging events on two of the three flights. These charging events cannot be explained using a simple charging model, and have implications towards the use of fixed bias Langmuir probes on sounding rockets investigating mesospheric altitudes. We show that for a reliable use of a single fixed bias Langmuir probe as a high spatial resolution relative density measurement, each payload should also carry an additional instrument to measure payload floating potential, and an instrument that is immune to spacecraft charging and measures absolute plasma density.